Ureide synthesis, accumulation and transport in Arabidopsis plants under salt and osmotic stress - Lescano, Ignacio (2013)
Fil: Lescano, Ignacio. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.